CAREGIVER SYNDROME IN MOTHERS OF ATYPICAL CHILDREN: AN INTEGRATIVE REVIEW. (Movimenta (ISSN 1984-4298), 2026)
Objective: To analyze Caregiver Syndrome in mothers of atypical children, identifying emotional, psychosocial, and structural impacts involved in continuous care through an integrative literature review. Methods: Integrative review following the steps proposed by Whittemore and Knafl (2005): problem identification, definition of eligibility criteria, database search, categorization, critical appraisal, and synthesis. Twelve references provided by the researcher were used, including articles, books, dissertations, and official documents. Results: The literature indicates high levels of stress, anxiety, and depression among caregiving mothers. Studies show that caregiver burden is related to the social role assigned to women, the lack of public and family support, and the intense therapeutic routine. Mothers perform multiple functions, experiencing physical and emotional exhaustion. Maternal loneliness and the insufficiency of inclusive policies exacerbate this strain. Conclusions: Caregiver Syndrome in mothers of atypical children is a multifactorial and widely neglected phenomenon. Intersectoral strategies are needed to provide emotional, financial, and social support to these women who bear a large part of the specialized care.
Keywords: atypical motherhood; caregiver syndrome; neurodivergence.